Severity of RSV infection in Southern European elderly patients during two consecutive winter seasons (2017–2018) - Boattini, Matteo (2022)
In Europe, the respiratory syncytial virus (RSV) surveillance system is very heterogeneous and there is growing evidence of the importance of RSV infections resulting in hospitalization of elderly patients. The aim of this study was to assess the severity of RSV infection in the elderly living in the aged Southern European countries. We conducted a retrospective study of elderly patients (≥65-year old) admitted for laboratory-confirmed RSV infection in three tertiary hospitals in Portugal, Italy, and Cyprus over two consecutive winter seasons (2017–2018). Uni-multivariable analyses were carried out to evaluate the effect of clinical variables on radiologically confirmed pneumonia, use of noninvasive ventilation (NIV), and in-hospital death (IHD). A total of 166 elderly patients were included. Pneumonia was evident in 29.5%. NIV was implemented in 16.3%, length of stay was 11.8 ± 12.2 days, and IHD occurred in 12.1%. Multivariable analyses revealed that the risk of pneumonia was higher in patients with chronic kidney disease (CKD) (odds ratio [OR]: 2.57; 95% confidence interval [CI]: 1.12–5.91); the use of NIV was higher in patients with obstructive sleep apnea or obesity hypoventilation syndrome (OSA or OHS) (OR: 5.38; 95% CI: 1.67–17.35) and CKD (OR: 2.52; 95% CI: 1.01–6.23); the risk of IHD was higher in males (OR: 3.30; 95% CI: 1.07–10.10) and in patients with solid neoplasm (OR: 9.06; 95% CI: 2.44–33.54) and OSA or OHS (OR: 8.39; 95% CI: 2.14–32.89). Knowledge of factors associated with RSV infection severity may aid clinicians to set priorities and reduce disease burden. Development of effective antiviral treatment and vaccine against RSV is highly desirable.